Persepsi Petani tentang Saluran Komunikasi Usahatani Padi - P. R. Pertiwi; A. Saleh (Jurnal Komunikasi Pembangunan, 2010)
Serang District is a one of four districts of Banten Province which resulted high production of paddy, at the westregion of Java Island. This condition must be defended with introduced paddy farming innovation continuously, whatsubmitted trough various of communication channel. The research objectives were: (1) to describe theinnovativeness characteristics of paddy farmers, (2) to know the perception of paddy farmers on extensioncommunication channel, (3) to analyze the relationship between the innovativeness characteristics of paddy farmerswith their perception about extension communication channels. This research was conducted with the survey methodsand observations in the three Serang subdistricts, including Ciruas, Carenang and Tirtayasa. The determination ofthe sample done in random sampling, with the number of samples of 136 people. The correlation analysis ofvariables is done through Spearman rank correlation test. Reasearch results were: the innovativeness characteristicsof paddy farmers were classified, except on the level of risk, including category bad; perception of farmers about thecommunication channels was good on the financing aspect, both interpersonal and media; farmer innovativenesscharacteristics correlated significantly with the perception of interpersonal and media communication channels,except ownership of capital